Diversity and Identity in the Workplace Connections and Perspectives - Villesèche, Florence (Springer International Publishing, 2018)
Examining the theoretical connections between identity and diversity, this new book explores how diversity management practices can be better informed by an enhanced understanding of the relationship between the two fields. Highlighting the relevance of identity to diversity studies, the authors concentrate on three key areas: social identity theory; critical perspectives on identity; and poststructuralist understandings. With the aim of fueling future research, this insightful book outlines a detailed research agenda and offers practical suggestions. Not only useful to academics, this book also seeks to encourage policy-makers and HR managers to develop current practices and make more research-informed management decisions.